2020
DOI: 10.4140/tcp.n.2020.549
|View full text |Cite
|
Sign up to set email alerts
|

Z-drugs and Falls: A Focused Review of the Literature

Abstract: OBJECTIVE: To provide a focused review of the literature related to the association between exposure to Z-drugs and the risk of falls, especially in the older population.<br/> DATA SOURCES: A literature search was conducted using Medline, PsychInfo, and the Cochrane Library database for all clinical trials, case series, and case reports published in English up to May 2020. The search terms used consisted of each Z-drug, including "zolpidem," "zopiclone," "eszopiclone," and "zaleplon," matched with "fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Internationally, several studies have been conducted in order to identify preventive strategies, including educational initiatives aimed at optimizing drug therapies in hospital environments, such as the more cautious use of loop diuretics, digitalis and digoxin, betablockers, and the so-called "Z-drugs" (comprising zolpidem, zoplicone, eszoplicone, and zaleplon) [38,39]. In addition, although an association between depression and the risk of falls is postulated, some authors also reported a relationship between selective serotonin reuptake inhibitors (SSRIs) and an increased risk of falls [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, several studies have been conducted in order to identify preventive strategies, including educational initiatives aimed at optimizing drug therapies in hospital environments, such as the more cautious use of loop diuretics, digitalis and digoxin, betablockers, and the so-called "Z-drugs" (comprising zolpidem, zoplicone, eszoplicone, and zaleplon) [38,39]. In addition, although an association between depression and the risk of falls is postulated, some authors also reported a relationship between selective serotonin reuptake inhibitors (SSRIs) and an increased risk of falls [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A despeito de ter um menor potencial de dependência, o uso dessa classe de medicamentos pode causar os mesmos efeitos adversos esperados para benzodiazepínicos. 19,20 Ademais, destaca-se que, recentemente a Food and Drug Administration (FDA) preconizou a inserção de informações nas caixas de medicamentos dessa classe (informação denominada Boxed Warning que apresenta destaque na embalagem de medicamentos dos Estados Unidos da América) referindo-se ao risco aumentado de lesões graves e morte em decorrência de comportamentos complexos do sono, incluindo sonambulismo. Esse efeito adverso pode ocorrer mesmo mediante uso de doses baixas, e até mesmo após o uso de apenas uma dose, com uso concomitante ou não de álcool ou outros depressores do sistema nervoso central.…”
Section: Discussionunclassified
“…Entretanto é importante destacar que esse resultado se limita a essa população específica e que outros estudos já identificaram tal associação em outros cenários. 19 Em relação ao desfecho fratura de fêmur, não se identificaram, na literatura, outros estudos longitudinais que investigaram sua associação com o uso de medicamentos sedativos entre pacientes idosos de um ambulatório de geriatria para fins comparativos. No presente estudo, o uso de sedativos e de benzodiazepínicos mostraram-se associados à incidência de fratura de fêmur no decurso de até 30 dias (OR = 2,57 para sedativos e OR = 3,45 para benzodiazepínicos).…”
Section: Discussionunclassified